Estacionalidad reproductiva en el vampiro común Desmodus rotundus (Cbiroptera, Phyllostomidae) en el Valle de Lerma (Salta, Argentina) - Núñez, H A (Universidad de Costa Rica, 1997)
The chiropteran reproductive parterns in tropical zones have been associated with food seasonality by synchronization between parturition time and the lrighest environmental productivity. In lhe common vampire ba, (Desmodus rotundus) whose food (catde blood), is widely available year round, reproductive seasonality mus! be absent. In order 10 test (his hypothesis, a natural cave colony in lhe Salta Province (Argentina), was studied. The vampire bate were captured with a mis! !le! placed al lhe cave enlrance. Reproductive condition in females (pregnancy, absence of pregnancy or lactation) and in males (abdonrinal or serotal tests) was seasonalty assessed with respect to temperature (surnmer, autom.n, winter, spring) anó hmnidíty (dry and wet seasons). Association between female reproductive condition and seasonality was detected. Tbe proportion of pregnancy and lactation were higher during spring and summer as well as al !he wet season. In males, there was no association between these variables. Although reproduction is continuous througout ¡he year, ir shows a marked seasonality. This pattern can be considered a result of environmcntal conditions (temperature anó hunridity) instead of food availability